Three Years Follow-up Results of Ranibizumab Treatment for Choroidal Neovascularization Secondary to Pathologic Myopia - Hefner, L.; Riese, J.; Gerding, H. (Klinische Monatsblätter für Augenheilkunde, 2013)
Background: Choroidal neovascularization (CNV) secondary to pathological myopia (PM) is one of the main causes of severe visual impairment in patients younger than 50 years. In this analysis we want to demonstrate the long-term results of Ranibizumab treating CNV secondary to PM.Patients and Methods: We retrospectively analysed 15 treatment naive eyes of 13 patients (10 women, 3 men, mean age: 61.5, SD 11.6, range: 41–80) with visual impairment due to CNV secondary to PM, which were treated with ranibizumab. Criteria for re-treatment were reduction of visual acuity and/or activity in OCT or fluorescence angiography.Results: We applied a mean of 3 injections (standard deviation [SD] 2.5, range: 1–8) ranibizumab during a mean period of 39.6 months (SD 5.3, range: 31–52). The spherical equivalent was − 12.4 diopters ± 4.1 (range − 7.5 to − 20.5 diopters). Before the first injection mean visual acuity (logMAR) was 0.69 ± 0.26. After one month visual acuity improved to 0.39 ± 0.23 (p = 0.002), after 3 months to 0.30 ± 0.22 (p = 0.002) and after 6 months up to 0.30 ± 0.22 (p = 0.002). After 12 months visual acuity was 0.30 ± 0.22 (p = 0.001) and after 24 months 0.30 ± SD 0.24 (p = 0.001). 11 patients reached a follow-up of at least 36 months and visual acuity was 0.30 ± 0.13 (p = 0,001).Conclusions: Treating CNV secondary to PM with ranibizumab during a follow-up of 36 months, we found considerable improvement of visual acuity. Compared to treatment of CNV secondary to exudative age-related macular degeneration, CNVs secondary to PM seem to respond faster to ranibizumab treatment and less injections are neccessary to reach stabilization.
Keywords: choroidale Neovaskularisationsmembran (CNV); pathologische Myopie; Ranibizumab; anti-VEGF